COVID-19 vs event tourism: utilizing technology as a solution? - Luh Yusni Wiarti; Setya Chendra Wibawa; Fitria Earlike Sani; Nyoman Dini Andiani (Universitas Merdeka Malang, 2023)
The COVID-19 pandemic that hit the world caused eventts in various countries to be canceled.Â Given the importance of eventts in tourism, this study aims to analyze the organization of eventts during the pandemic: how technology plays an important role in eventts and the eventt model that eventt organizers and participants prefer. A qualitative approach was used by presenting the results of in-depth interviews and the study of documents and literature related to the study. The study concluded that technology has been used in various tourism eventts abroad including in Indonesia. 'Virtual' eventts are still a debate between 'love' and 'hate' about the experience gained by participants, the costs incurred, and the multiplier effect received by the destination. Virtual Face to Face (VFF) is a new genre for eventts in Ubud Bali with the priority eventt model being the preferred VFF Art, Culture, and Entertainment event.